Zanzibar. Some nineteenth-century Arabic writings on healing - Declich, Lorenzo (The transmission of learning in Islamic Africa, 2004)
Much on Emily Said-Ruete’s Memoirs of an Arabian princess. Then on MSS and books on tradtional medicine and magic, found in the Zanzibar National Archives.
Keywords: Catalogue -- Zanzibar

The Arabic manuscripts of the Zanzibar National Archives: a checklist - Declich, Lorenzo (Rivista degli studi orientali, 2006)
Keywords: Catalogue -- Zanzibar